Comprehending Relations and Functions: Introducing and Demonstrating Papan Resi Teaching Aid - Meiva Marthaulina Lestari Siahaan; Lailin Hijriani; Talisadika Maifa; Yosepha Patricia Wua Laja; Yohanis Ndapa Deda (Smart Society, 2022)
The teachers need help to convey the differences between relations and functions and to make concrete examples. The purpose of the community service team is to help students find and comprehend the theory and concept about relations and functions material for grade 8 by introducing and demonstrating the Papan Resi visual aid.The service held in SMPK Aloysius Niki-Niki, Timor Tengah Utara District, Nusa Tenggara Timur. The service method is based on action research: planning, action, observation, and reflection. The data are collected based on the audiences' observation sheets and response sheets. Data analysis used data triangulation. The results of this community service are that introducing and demonstrating Papan Resi could be beneficial for increasing students' comprehension of SMPK Aloysius Niki-Niki. The constructivist situation influences it, and the service needs to be held for other teaching aids